5-HT4 receptor agonist effects on functional connectivity in the human brain: implications for procognitive action - de Cates, AN; Martens, MAG; Wright, LC; Gibson, D; Spitz, G; Gould van Praag, CD; Suri, S; Cowen, PJ; Murphy, SE; Harmer, CJ (Elsevier, 2023)
Background: Cognitive deficits are often comorbid with mood disorders and can cause significant functional impairment even after resolution of the primary mood symptoms. We do not currently have pharmacological treatments that adequately address these deficits. 5-HT4 receptor agonists show promise as potential procognitive agents in animal and early human translational studies. Optimal cognitive performance in humans is directly associated with appropriate functional connectivity between specific resting-state neural networks. However, so far the effect of 5-HT4 receptor agonism on resting-state functional connectivity (rsFC) in the brain in humans is unknown. Methods: We collected resting-state functional magnetic resonance imaging scans from 50 healthy volunteers, of whom 25 received 6 days × 1 mg prucalopride (a highly selective 5-HT4 receptor agonist) and 25 received placebo in a randomized double-blind design. Results: Network analyses identified that participants in the prucalopride group had enhanced rsFC between the central executive network and the posterior/anterior cingulate cortex. Seed analyses also showed greater rsFC between the left and right rostral anterior cingulate cortex and the left lateral occipital cortex, and reduced rsFC between the hippocampus and other default mode network regions. Conclusions: Similar to other potentially procognitive medications, low-dose prucalopride in healthy volunteers appeared to enhance rsFC between regions involved in cognitive networks and reduce rsFC within the default mode network. This suggests a mechanism for the behavioral cognitive enhancement previously seen with 5-HT4 receptor agonists in humans and supports the potential for 5-HT4 receptor agonists to be used in clinical psychiatric populations.